The role and impact of artificial intelligence on social science and humanities - Nguyen Hong Anh (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2025)
Artificial Intelligence (AI) currently is growing at “a rapid pace” with several significant contributions to manufacturing, business, service and human life. However, AI is a very complicated field which also poses many worried challenges. A proper understanding of AI to grasp correctly and promptly the opportunities and challenges from AI is essential for every person, every organization, as well as every country. AI plays a significant role and has a significant impact on social science and humanities research. We need to have a more comprehensive view to promote the positive aspects of AI and reduce the limitations that AI can cause. Code: 24102802